Barriers to HIV Care and Treatment by Doctors: A review of the literature - P. Naidoo (South African Family Practice)
Introduction: Over the last two decades acquired immunodeficiency syndrome (AIDS) has emerged as one of the most serious public health problems in the world, and by the end of 2003 it was estimated that 5.3 million South Africans were human immunodeficiency virus (HIV) positive, which corresponds to 21.5% of the population.1 In the early phase of the HIV epidemic few doctors saw infected patients and treatment options were limited. As a result many doctors were reluctant to provide care to HIV infected patients and homophobia amongst doctors, fear of contact with patients and unwillingness to care were frequently reported.2 However, there has been an exponential increase in the number of HIV and AIDS related cases and more doctors are encountering infected individuals. This review summarizes our current knowledge of barriers to treatment of HIV infected patients by doctors.